Acoustic power suppression of a panel structure using H∞ output feedback control - Sivrioglu, S; Tanaka, N; Yuksek, I (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2002)
This paper presents a robust control system design for suppressing the radiated acoustic power emitted from a vibrating planar structure, and spillover effect caused by neglected high-frequency modes. A state-space model of a simply supported panel structure is derived and an output equation is formed based on the one-dimensional PVDF film sensors. An output feedback H-infinity control is designed by introducing a multiplicative perturbation which represents unmodelled high-frequency dynamics in the control system. The simulation and experimental results demonstrated significant decrease in sound radiation for the considered structural power modes in control. (C) 2002 Academic Press.
Keywords: PIEZOELECTRIC FILM SENSORS; ACTIVE CONTROL; RADIATION; Acoustics; Engineering; Mechanics